How to Allocate Resources in Times of Pandemic? What Justice? - Ledolledec, Eloïse; Kermaïdic, Raphaël (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
If the question of the fair distribution of resources has been faced by societies since antiquity, the question of the fair distribution of medical resources takes on a whole new dimension in the context of the current global pandemic. This round table attempts to analyze and understand how to reconcile the principles of distributive justice in conditions of limited resources. It opens up a broader reflection on the fundamental difference between ethical or political decision making at the patient level and at the macroscopic level. Finally, a discussion guides us to reflect on the autonomy of patients and the legitimacy of resuscitation – for those who do not wish to continue living – on the value of “saving at all costs” and the place of triage in the practice of medicine.